Energy-optimized control of HVAC systems with recirculation and heat recovery in cleanrooms - Jakubiak, Monika; Porowski, Mieczysław (Instal, 2021)
The article presents algorithms of energy-optimal control of a standard HVAC system with recirculation, heat recovery (rotary energy regenerator) and a dry cooler in a recirculation cycle for a cleanroom ISO5 (M3.5, cl. 100). The annual demand for usable, final and primary energy was determined for thermodynamic air treatment and the case of real loads and operating parameters, as well as two control variants: standard – variant I and energy-optimal – variant II. A simulation model of the HVAC system operation throughout the year was formulated as an analysis tool. It has been shown that the implementation of energy-optimal control algorithms (variant II) allows to reduce the annual primary energy demand of the HVAC system by as much as 39.2% compared to the standard strategy (variant I).
Keywords: energy-optimal control; HVAC systems; cleanrooms